A Novel Loop Based Fine Grained Network-wide Time Synchronization over Constrained Delay Paths in Wireless Sensor Networks - et. al., K L V Sai Prakash Sakuru, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sensor Networks play a vital role in today’s ever-growing automation process. Time synchronization between the nodes impacts the performance of the network and applications. Most of the existing time synchronization algorithms either run a tree algorithm or cluster-based algorithm and then perform time synchronization. Both the algorithms suffer from communication and computation efficiency. When a node fails due to an energy shortage, these algorithms need to rerun the setup, thereby the remaining nodes consume energy. Hence, we propose a novel loop-based fine-grained network-wide time synchronization over constrained delay paths for the sensor networks. When a packet is transmitted, the neighborhood node on receiving this packet will add a time offset information and broadcast. The process continues until the loop is formed and then uses the information set and helps to synchronize its clock information. The simulations and results validate the performance of the proposed algorithm.